Sex differences in cognition, anxiety-phenotype and therapeutic effect of metformin in the aged apoE-TR mice - Yingbin Lin; Xinqun Luo; Fangyu Wang; Huange Cai; Yuanxiang Lin; Dezhi Kang; Wenhua Fang (Biology of Sex Differences)
Abstract Background Apolipoprotein E4 (ApoE4) is associated with an increased risk of Alzheimer’s disease (AD), depression, and anxiety, which were reported to improve after the administration of metformin. However, sex influence on the effect of ApoE4 and metformin on cognition and mental health is poorly understood. Methods ApoE3-TR and apoE4-TR mice of both sexes were randomly assigned to the normal saline and metformin groups from 13 months to 18 months of age. Behavior tests (MWM, EPM, OFT, TST, FST) were conducted to assess cognition, anxiety, and depression-like behaviors. The mice’s blood glucose was also recorded. Results Male aged apoE4-TR mice are more vulnerable to cognitive decline than females. Metformin improves the spatial memory of female, but not male apoE3-TR mice and female apoE4-TR mice while aggravating the cognitive impairment of male apoE4-TR mice. The anxiety-like phenotypes in male apoE4-TR mice are more severe than in male apoE3-TR mice, while metformin ameliorates the anxiety-like behaviors in the male apoE4-TR mice but not in male apoE3-TR mice. In addition, metformin alleviates depression-like behaviors in male and female apoE4-TR mice. The hypoglycemic effect of metformin is insignificant in both male and female apoE4-TR mice. Conclusions Male sex exacerbates APOE4-related cognitive impairment and anxiety in aged mice and is insensitive to the cognition improvement effect of metformin in the aged apoE3 mice. Male sex with APOE4 may experience more severe cognitive impairment after treatment with metformin while sensitive to the anti-anxiety effects of metformin. These findings identify sex-specific effects on ApoE4-based dementia, anxiety prevention, and therapy, emphasizing the importance of further sex dimension analyses in vivo and clinical studies.